2022
DOI: 10.1111/jpi.12791
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated daytime melatonin secretion on a simulated night shift schedule generates a distinctive 24‐h melatonin rhythm with antiphasic daytime and nighttime peaks

Abstract: The daily rhythm of plasma melatonin concentrations is typically unimodal, with one broad peak during the circadian night and near‐undetectable levels during the circadian day. Light at night acutely suppresses melatonin secretion and phase shifts its endogenous circadian rhythm. In contrast, exposure to darkness during the circadian day has not generally been reported to increase circulating melatonin concentrations acutely. Here, in a highly‐controlled simulated night shift protocol with 12‐h inverted behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Interestingly, in the same randomized cross‐over trial, individuals with a MTNR1B diabetes risk variant exhibited a stronger degree of impaired glucose tolerance after late eating at night 203 . Low nocturnal melatonin levels have also been associated with impaired glucose tolerance and insulin resistance 204,205 and an increased risk of type 2 diabetes, 206 while high melatonin levels during daytime sleep in shift workers were associated with impaired glucose tolerance 207 . In a cross‐sectional study in adolescents with obesity, a low nocturnal melatonin concentration was associated with insulin resistance 208 .…”
Section: Restoration Of Circadian Synchronymentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, in the same randomized cross‐over trial, individuals with a MTNR1B diabetes risk variant exhibited a stronger degree of impaired glucose tolerance after late eating at night 203 . Low nocturnal melatonin levels have also been associated with impaired glucose tolerance and insulin resistance 204,205 and an increased risk of type 2 diabetes, 206 while high melatonin levels during daytime sleep in shift workers were associated with impaired glucose tolerance 207 . In a cross‐sectional study in adolescents with obesity, a low nocturnal melatonin concentration was associated with insulin resistance 208 .…”
Section: Restoration Of Circadian Synchronymentioning
confidence: 98%
“…203 Low nocturnal melatonin levels have also been associated with impaired glucose tolerance and insulin resistance 204,205 and an increased risk of type 2 diabetes, 206 while high melatonin levels during daytime sleep in shift workers were associated with impaired glucose tolerance. 207 In a cross-sectional study in adolescents with obesity, a low nocturnal melatonin concentration was associated with insulin resistance. 208 In addition, a shorter interval between dim-light melatonin onset and sleep onset has been associated with higher fasting insulin and HOMA-IR.…”
Section: Melatoninmentioning
confidence: 99%
“…Its secretion increases with weak light stimulation at night but decreases in the daytime (Carstensen et al, 2022). The rhythmic regulation of melatonin affected the metabolism of nutrients, including carbohydrates, lipids and proteins, indicating the important role of melatonin in maintaining body functions (Kent et al, 2022;Qian et al, 2022). A previous clinical study demonstrated the protective effect of melatonin in rhythmic secretion on bone metabolism in postmenopausal women (Ostrowska et al, 2001b).…”
Section: Clinical Datamentioning
confidence: 99%
“…Night work is a special category that should be mentioned. Such individuals could be at increased risk because an additional MT peak is prevalent during daytime sleep, complementary to the anticipated peak at the circadian night, leading to higher 24-h glucose levels [51]. This may partially explain the increased incidence of T2DM in female nurses who work on night shifts [52].…”
Section: Mt and Glucose Homeostasismentioning
confidence: 99%